Pengaruh Senam Kegel terhadap Inkontinensia Urin pada Ibu Post Partum di PMB Nuri Kota Jambi - Dea Gita Ramadilla; Herinawati Herinawati; Diniyati Diniyati; Sri Yun Utama (Universitas Baiturrahim, 2022)
Many postpartum women experience urinary incontinence due to an injury during delivery or it is called pressure urinary incontinence because it is closely related to vaginal delivery due to the lowering of the baby's head, causing pelvic floor dysfunction. In Indonesia, the incidence of urinary incontinence in postpartum mothers is 34.1% in the first 6 weeks postpartum and decreases to 27.7% after the postpartum period. Exercise that aims to strengthen the periurethral and vaginal muscles of the mother so that they can function optimally again. This research is a type of pre-experimental research using the One Group Pretest-Posttest design. The population were all postpartum mothers in PMB Nuri Jambi City, which amounted to 119 respondents (in January-March), taking samples using the Accidental Sampling technique as many as 41 respondents. This research was conducted at PMB Nuri Jambi City in June 2021 - July 2021. The data processing in this study used univariate and bivariate analysis and the Shapiro Wilk statistical test because the data were normally distributed with p-value > 0.05. The results of this study using the T test obtained p-value = 0.000 <0.05. Which shows there is an effect of Kegel exercises on urinary incontinence before and after being given Kegel exercises. Based on the results of the study, it can be concluded that Kegel exercises can prevent urinary incontinence in postpartum mothers.